Socio-Cultural Influencing Factors Among Mothers Knowledge About Immunization Dropout of Children Under Five Years at Rural and Urban Area: A Comparative Study - Shehab Abboud, Malik; Abdul Redha Hasan, Abdul Mahdi (Journal of Neonatal Surgery, 2025)
Background: Vaccination of children is a vital part of worldwide health systems because it is the most successful and cost-effective preventive clinical service for children's health and for the maintenance of public health. Vaccines stimulate the body’s own immune system to protect the person against subsequent infection or disease. The aims: to identify the Socio-cultural factors influencing immunization dropout among mothers of children under five years, and to compare between the rural and urban area with regards to the factors influencing immunization dropout among children under five years Methods: A cross-sectional descriptive study design, conducted in Babylon province from October 4, 2023, to July 1, 2024. Non Probability " convenience " sample of (303) mothers who have children under five years were selected from unit of immunization at primary health care centers (PHCCs), from Babylon province. Result of the study: Overall, urban mothers had good knowledge about immunization, whereas rural mothers had poor knowledge, and the comparison between mother’s Socio-cultural- knowledge Influencing of Immunization Dropout of both group (urban and rural) the recorder mean score shows high significant differences between the responses. Conclusion & recommendation: Most mothers in both groups received information about childhood immunization from healthcare workers. The findings revealed that overall assessment of mothers live in urban had good knowledge about immunization, whereas rural mothers had poor knowledge. Regarding to the recommendation, develop and expand SMS reminder systems to improve vaccination adherence. Conduct future studies on a larger sample and at a national level to improve postnatal care services.